MODIFIKASI TERMINAL BLOK TRAINING UNIT SMC MAP 202 - , ANDRI ARMANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In college studying process especially in automation control pratice where control technology always developing and get inovation so pratice equipment also must be following the development of technonolgy. For make easy college to learning and to minimalizimg the fals on a cotroller wiring so modifikation is needed on the training unit that claimed new and complex. To solving that problems therefore has to be done by modification on training unit thats claimed complex. Changing on terminal block that not uniform and hard to undestand has changed with terminal block quick release plug that more simple, easy to learn, more uniform and also the wiring on training unit SMC MAP 202. Visually result from modification terminal block training unit SMC MAP 202 look more simple and uniform so easy for college for learning the components. And on process the result from modification terminal block training unit SMC MAP 202 can be operate without trouble on sensor, actuator and PLC program.